2007
DOI: 10.1007/s11255-006-9158-6
|View full text |Cite
|
Sign up to set email alerts
|

Pathological review of internal genitalia after anterior exenteration for bladder cancer in women. Evaluating risk factors for female organ involvement

Abstract: To evaluate cancer involvement of internal female genitalia of patients undergoing anterior exenteration for clinically organ confined transitional cell carcinoma of the bladder, and identify potential preoperative risk factors. Charts and anterior exenteration specimens from 54 women with clinically organ confined transitional cell bladder cancer were retrospectively reviewed. Emphasis was given to the presence of internal genitalia involvement and or primary gynecologic pathology. Unsuspected internal genita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 24 publications
3
21
0
Order By: Relevance
“…Consistent with the present findings, Varkarakis et al [18] reported unsuspected involvement of internal genitalia in only 3 (5.6%) out of 54 women with clinically organ-confined transitional cell bladder cancer. The vagina was involved in 2 (3.7%) cases and the uterus in 1 (1.9%).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Consistent with the present findings, Varkarakis et al [18] reported unsuspected involvement of internal genitalia in only 3 (5.6%) out of 54 women with clinically organ-confined transitional cell bladder cancer. The vagina was involved in 2 (3.7%) cases and the uterus in 1 (1.9%).…”
Section: Discussionsupporting
confidence: 92%
“…In all cases, involvement was due to direct extension from bladder tumors of the base and dome. Benign pathology of the reproductive organs was observed in 6 (11.5%) women and involved the uterus in all cases [18]. Ali-El-Dein et al [19] reported gynecologic organ involvement in 16 (2.6%) of 609 patients; no primary genital cancers were detected in this group of women.…”
Section: Discussionmentioning
confidence: 83%
“…Similar fi ndings were reported by Varkarakis et al (2007), who found internal genitalia involvement in only three patients out of 54 women with clinically organ-confi ned transitional cell bladder cancer. Th e vagina was involved in two cases (3.8%) and the uterus in one (1.9%).…”
Section: H Salem and A El-maznysupporting
confidence: 89%
“…Metastasis of urothelial carcinoma to the uterus is very rare. 23,24 Metastasis of colorectal cancer to the genital tract is described. 25 No information is available on the risk for Crohn diseaseYrelated metastases.…”
Section: Discussionmentioning
confidence: 99%